(untitled) (International journal of artificial intelligence, 2026)
This paper analyzes the role of Islamic values in social life and their integration with the reforms of New Uzbekistan. Islamic moral principles are considered an important factor in shaping high human qualities such as humanism, justice, honesty, and tolerance. The study also highlights the contribution of religious values to social stability and national development in the context of ongoing social, spiritual, and legal reforms in New Uzbekistan. The research reveals the scientific correlation between Islamic values and modern reform processes.